Cursing Smertuccus: Some Thoughts on the (Mis)Use of the Patronymic in Latin Defixiones - Sánchez Natalías, Celia (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
This paper focuses on a defixio against Smertuccus, a text that was found in modern-day Vechten (Fectio, Germania Inferior) under unknown circumstances. This extremely concise inscription was written in capitals following an unusual ordinatio, which runs from bottom to top and right to left. The curse, which written for unknown reasons, merely contains the cognomen of the target together with his paternal filiation. This contribution offers some considerations on these features (i.e. the layout and the presence of the patronym), which are rarely attested among Latin defixiones from the Roman West.